MicroRNAs as novel predictive biomarkers and therapeutic targets in colorectal cancer - Stiegelbauer, Verena (Baishideng Publishing Group Inc, 2014)
Colorectal cancer (CRC) is the third most common cancer in western countries. Despite significant improvement in available treatment options, CRC still remains the second leading cause of cancer-related death. Traditionally, 5-fluorouracil has been used as the main chemotherapy drug for treatment of metastatic CRC (mCRC). However, during the last two decades more effective chemotherapeutic agents such as oxaliplatin, irinotecan and the monoclonal antibodies cetuximab, panitumumab and bevacizumab have been used in clinical practice. More recently, the therapeutic armamentarium has been supplemented by the monoclonal antibodies bevacizumab, cetuximab and panitumumab as well as the protein-trap aflibercept and the small molecule multi-kinase inhibitor regorafenib. One of the major problems for the management of CRC is the inherent or acquired resistance to therapeutic approaches. The discovery of microRNAs (miRNAs), a class of small, endogenous, non-coding, single-stranded RNAs that play a role as post-transcriptional regulators, has added new dimensions to the diagnosis and treatment of cancer. Because miRNAs are important regulators of carcinogenesis, progression, invasion, angiogenesis and metastases in CRC, they might serve as potential predictive and prognostic factors and even as therapeutic targets themselves. Several miRNAs are already known to be dysregulated in CRCs and have been linked to biological processes involved in tumor progression and response to anti-cancer therapies. This review summarizes current therapeutic approaches for treating CRC and highlights the role of miRNAs as novel predictive biomarkers and potential drug targets in CRC patients.